Liver Specific Serum Micro RNA122 as a Prognostic Marker in Egyptian Patients with Liver Cirrhosis - Mona A Amin; Mai Fawzi; Dina Sabri; Heba Sedrak; Shrouk Mausa; Abdelaziz El-Saadi (Archives of Hepatitis Research - Peertechz Publications, 2017)
Introduction: Recent research has shown that microRNAs (miRNA) are emerging as important regulators of cellular differentiation. The miR-122 accounts for approximately 70% of all miRNAs in the liver so its presence in the serum is highly indicative of liver processes. Aim of the work and methods: was to study the role of miR-122 as a prognostic new marker in patients with liver cirrhosis. MiR-122 was detected by quantitative real-time reverse transcription (RT)- PCR  technique. Eighty patients with liver cirrhosis were included in our study, we divided them into 4 equal groups according to the complications of liver cirrhosis (1-compensated cirrhotics, 2- cirrhotics with ascites, 3-spontaneous bacterial peritonitis (SBP), and 4- hepatorenal syndrome (HRS) group) to evaluate if the serum level of miR-122 might be a suitable parameter for assessment of disease severity and prognosis in such patients. Results: miR-122 was statistically signifi cantly higher in group 1 "compensated" when compared to both groups 2 "ascites" and 3 "SBP" (P=0.001), while the difference was highly signifi cant when compared to its level in group 4 ''HRS'' (P<0.001). Serum miR-122 levels were positively correlated with serum albumin, PC, and serum Na levels while it was negatively correlated with creatinine, urea, and INR. Also there was strong negative correlation between serum miR-122 level and both MELD and Child score. Conclusion: Lower serum miR-122 levels are associated with ascites, spontaneous bacterial peritonitis and hepatorenal syndrome. Therefore, serum miR-122 could be a new potential parameter and a prognostic marker in patients with liver cirrhosis.